STEREOMETRIYALÍQ MÁSELELERDI SHESHIWDEGI ÁHMIYETLI BAYLANÍS - Daniyarova, S.M. (SCIENCE and SOCIETY, 2021)
The article deals with conception of the space and its’ positive influence to development of the students. More over, investigated the most important connections of the solution of stereometric problems and analyzed by examples.